Pilot testing of LoRaWAN technology in disconnecting fuse boxes - Benešl, L.; Mlýnek, P.; Harman, D. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
This article deals with the concept of Smart Cities concerning Smart Grids. As part of Smart Grids and secondary metering, there is also the lifespan of the devices that are deployed in distribution companies. This also applies to switch cabinets, disconnecting fuse boxes (DFB), and other elements that are made of a material that can degrade due to adverse weather conditions. For this reason, secondary temperature and humidity measurements have been introduced. During the measurements, temperature extremes were recorded, which could reach more than -10 °C in winter months and almost 45 °C in the warm months. Humidity could reach up to 100 % in some cases. Another monitored parameter was the successfully received messages, where LoRaWAN technology reached almost 95 %.
Keywords: Smart Grids; LoRaWAN; temperature and humidity measurement; weather conditions